Analysis of broncho alveolar lavage adenosine deaminase assay in patients with clinically diagnosed pulmonary tuberculosis - Deep Rajendrabhai Kothari; Nilesh Dutt; Palak Prajapati; Pankaj Garg; Mamta Patel (Medical Laboratory Journal)
Background: The sputum smear-negative pulmonary tuberculosis (PTB) is a diagnostic challenge for physicians. It has been shown that adenosine deaminase (ADA) activity increases in various body fluids of patients with tuberculosis (TB). A prospective clinical trial was conducted to determine the effectiveness of ADA activity in bronchoalveolar lavage (BAL) in subjects who have sputum smear-negative PTB. Methods: A total of 29 patients (M/F: 15/14), mean age (36.8 years), were enrolled in our study from October 2021 to August 2022 after providing written consent. The mean duration of symptoms was 41.66 days. Out of 29 patients, 21 patients had BAL ADA 4.81±1.68 unit??, for whom AKT treatment was started and cured, while four patients with BAL ADA 4.50±2.86 unit? did not improve, and four patients with BAL ADA 6.52±1.16 whose AKT treatment is ongoing at present but clinically improved. The sensitivity of BAL ADA with the outcome of 29 patients is 75%, while for BAL CBNAAT, it is 80%. When we apply a formula for combined sensitivity for the parallel test, then it comes to 95%, which indicates a great number of patients gets the benefit when we apply both tests simultaneously. Results: We conclude that ADA activity was significantly increased in BAL. Conclusion: BAL ADA is a useful and effective investigation for the diagnosis of PTB.